A combinational treatment of carotenoids decreases Aβ secretion in human neurons via β-secretase inhibition. (September 2020) - Sho, Misato; Ichiyanagi, Naoki; Imaizumi, Kent; Ishikawa, Mitsuru; Morimoto, Satoru; Watanabe, Hirotaka; Okano, Hideyuki
Highlights: Human iPSC-derived cortical neurons are a suitable in vitro model for drug screening. Carotenoids, but not DHA, decrease Aβ secretion in human neuronal cultures. β-Secretase activity is specifically inhibited by carotenoid treatment. Abstract: Alzheimer's disease (AD) is the most common cause of dementia and is characterized neuropathologically by the presence of amyloid plaques and neurofibrillary tangles. Amyloid-β (Aβ) peptides, major components of amyloid plaques and crucial pathogenic molecules in terms of the amyloid hypothesis, are derived from successive proteolytic processing of amyloid-β precursor protein (APP). In this study, we established a human neuronal culture system using induced pluripotent stem cells (iPSCs) to evaluate the possible effects of natural compounds on the amyloid phenotype. Unexpectedly, we found that combinational treatment of carotenoids, but not docosahexaenoic acid, significantly decreased Aβ secretion from iPSC-derived human cortical neurons. Importantly, the effects of the carotenoids resulted from specific inhibition of BACE1 activity and not from expression changes in APP or BACE1. Therefore, these results indicate a novel beneficial function of carotenoids in the anti-amyloidogenic processing of APP. Collectively, this study will shed light on neuronal protection by a novel mechanism during the pathogenesis of AD.